Violence Without Touch: Rethinking Debt Collection Practices Through Human Dignity Principles and Legal Ethic Frameworks - Handriyanto Wijaya; Dewi Sulistianingsih; Irawaty Irawaty (Universitas Islam Sultan Agung, 2026)
The rapid expansion of financial technology lending services in Indonesia has significantly transformed debt collection practices from conventional direct collection methods into indirect forms of coercion conducted through digital communication and social pressure. In practice, debt collection activities increasingly involve persistent intimidation, threatening communications, and the misuse of personal data, often affecting individuals within the debtor’s social sphere. Consequently, private financial obligations are exposed to broader public scrutiny, resulting in psychological distress, reputational damage, fear, and social exclusion. This research examines such practices as a form of non-physical coercion operating through psychological and social mechanisms. This study employs a normative legal research method through the examination of Indonesian statutory regulations, regulatory frameworks, and relevant legal doctrines concerning debt collection practices and personal data protection. The findings demonstrate that coercive non-physical debt collection practices have become increasingly prevalent within digital lending systems, particularly through the dissemination and exploitation of personal data as a means of exerting social pressure upon debtors. Furthermore, the involvement of third parties intensifies coercive circumstances and increases the potential violation of human dignity and privacy rights. Nevertheless, the existing legal framework remains fragmented, compliance-oriented, and inadequate to effectively address the substantive harms arising from such practices. Accordingly, this research proposes a dignity-based legal assessment framework emphasizing proportionality, personal data protection, accountability, and humane standards of debt collection in order to promote fair, lawful, and responsible financial technology practices.